Lifeworlds of Islam: The pragmatics of a religion. MohammedBamyeh. Oxford University Press, 2019. - SADEK, KARIM (My University, 2022)
In the past 120 years, there have been 32,400 scholarly contributions on the Haitian Revolution. Two thirds of these were published in the past 20 years alone. This volume of published scholarship contrasts sharply with the more than 2 million outputs on the French Revolution over the same period. An intellectual revival seems afoot; perhaps the first concerted generational effort defying a longer tendency of scholastic occlusion vis-à-vis the Haitian Revolution. The upsurge in scholarship includes David Geggus’ 1982 work on the Revolution’s impact in the Atlantic World, which he followed with the Revolution’s documentary history in 2014. There has also been Sibylle Fischer’s 2004 Modernity Disavowed: Haiti and the Cultures of Slavery in the Age of Revolution, Laurent Dubois’ 2005 Avengers of the New World: The Story of the Haitian Revolution, and, belatedly in 2018, Julius S. Scott’s The Common Wind: Afro-American Currents in the Age of the Haitian Revolution. Not to mention articles in such outlets as the Journal of Intercultural Studies, Political Theory by established scholars (Gurminder Bhambra), and newer voices (such as Adom Getachew) all keen to buck the historical trend. All of these, of course, build on C.L.R James’ Black Jacobins, first published in 1939. Eduardo Grüner’s argument is simple and, for those who have been attentive to the growing scholarship on the topic, familiar enough: the historic and continuing significance of the Haitian Revolution has not only been ignored but persistently negated, particularly in democratic theory. Predictably, Grüner’s contribution is a full-frontal charge leveled at Western political theory. The book’s distinctiveness lies elsewhere and is threefold. First, his is a dialogue principally with Latin American critical and especially postcolonial scholars who, much like their Euro-American counterparts, have been just as blind to the importance of the Haitian Revolution. Given that it was the most far-reaching and successful decolonial struggle in the Atlantic, its muted intellectual reception in the context of numerous bi-centennial independence celebrations in Latin America, he argues, tells us something about blackness in the world today. As reflected in the book’s title, a key concept in Grüner’s treatment of the Haitian Revolution is that of counter-modernity, which is central to his critique of the various “posts” (postmodernism, poststructuralism, postcolonialism) and even decoloniality. For Grüner, there is no escaping or transcending (European) modernity: a singular, global systemic phenomenon. Accordingly, there cannot be multiple, adjacent, and autonomous modernities precisely because capitalist accumulation has drawn multiple continents into a single but stratified whole. In addition, despite rhetorical gestures toward transcending modernity, there is no common experience of its dividend. A dividend, Grüner insists, mainly proscribed to white, European men. The Haitian Revolution exposed liberalism’s partial scope; that is, it revealed and countered the Enlightenment’s limited and fundamentally unequal modernity with a philosophically and ontologically expansive one. Thus, when Grüner invokes counter-modernity, he calls for countering this restricted, uneven version of modernity. For him, the baby and the bathwater must and can be remade, that is, modernity and its philosophical underpinnings can and must be constituted anew in how the Haitian Revolution tried to do. Additionally, for Grüner, modernity can only fully realize its possibilities—philosophically and materially—from within itself, globally distributing these more equitably while simultaneously confronting its partialities. Accordingly, it is from within its material base in the way that Haiti’s slave plantations formed the foundation for the French bourgeoisie’s emergence that we can counter our current modernity.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)